Microbial - Planktonic foodweb dynamics of a eutrophic Area of Concern: Hamilton Harbour. Issue 3 (3rd July 2017) - Munawar, M.; Fitzpatrick, M.
Abstract : Hamilton Harbour, located on the western end of Lake Ontario, has a long history of cultural eutrophication as well as industrial contamination. We explored the structure and function of the microbial – planktonic foodweb during the growing seasons (May–October) of 2004 and 2006 in order to consider the flow of autochthonous production from lower to higher trophic levels. Our analyses included microscope based assessments of bacteria, heterotrophic nanoflagellates, ciliates, phytoplankton and zooplankton as well as radioisotope based measurements of primary productivity and bacterial growth. While routine measures of total phosphorus (avg: 25–33 µg l −1 ) and chlorophyll a (avg: 12–15 µg l −1 ) were indicative of eutrophy, mean phytoplankton biomass in 2004 (2.0 g m −3 ) and 2006 (2.2 g m −3 ) suggested mesotrophic conditions. However, the appearance of algal blooms in the summer of 2006 was an obvious indicator of cultural eutrophication. With respect to the microbial – planktonic foodweb, the organic carbon pool increased from a mean of 757.5 mg C m −3 in 2004 to 1160.3 mg C m −3 in 2006 and this increase was almost evenly split between autotrophs (198.7 mg C m −3 ) and heterotrophs (204.1 mg C m −3 ). The increased autotrophic carbon is readily attributable to the observed algal blooms driven by warmer temperatures and higher concentrations of soluble reactive phosphorus. However, the increase in heterotrophic carbon, primarily heterotrophic nanoflagellates, was apparent from the earliest observations in 2006 and remained consistently high throughout the year. We hypothesize that the increased heterotrophic carbon was the consequence of increased allochthonous carbon being shunted through the microbial foodweb; the energy generated was not likely transferred to zooplankton and passed on to higher trophic levels. More research into the dynamics of allochthonous and autochthonous carbon in eutrophic environments is called for.